ANALISIS PENGARUH CITRA MEREK, INOVASI PRODUK DAN PERIKLANAN TERHADAP KEPUTUSAN PEMBELIAN AQUA (STUDI KASUS PADA MAHASISWA/I STIE-IBEK PANGKALPINANG) - Lonita, Novitasari; Panjaitan, Fery; Mulyani, Hendarti Tri Setyo (Jurnal Progresif Manajemen Bisnis, 2023)
This study aims to determine how much influence the image has brand, product innovation and advertising on AQUA purchasing decisions on STIE-IBEK Pangkalpinang students partially and the influence of brand image, product innovation and advertising on AQUA purchasing decisions on STIE-IBEK Pangkalpinang students simultaneously. This research method uses a quantitative descriptive approach. The population in this study were STIE-IBEK Pangkalpinang students, where the sample was 70 respondents who were determined using the purposive sampling technique. The data collection technique was carried out by means of a questionnaire. Data is processed using JASP (Jeffrey’s Amazing Statistics Program). The results showed that (1) brand image has a partial positive effect on purchasing decisions with a significance value of 0.001 > 0.05 and a tcount of 11.633 > a ttable value of 1.99547. (2) Product innovation has a partial positive effect on purchasing decisions with a significance value of 0.001 > 0.05 and a tcount of 5.788 > of a ttable value of 1.99547. (3) Advertising has a partial negative effect on purchasing decisions with a significance value of 0.001 > 0.05 and a tcount of -4.502 < a ttable value of 1.99547. (4) Brand Image, Product Innovation and Advertising simultaneously have a positive effect on Purchasing Decisions with a significance value of 0.001 < 0.05 and an fcount value of 315,137 > rather than a ftable value of 2.74.